2019
DOI: 10.1186/s12906-019-2482-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the α-glucosidase inhibitory potential of methanolic extracts of traditionally used antidiabetic plants

Abstract: BackgroundDifferent plant parts of Roylea cinerea (D. Don) Baill. (Lamiaceae), Clematis grata Wall. (Ranunculaceae), Cornus capitata Wall. (Cornaceae) are traditionally used in the management of diabetes and various other diseases.MethodThe air-dried plant parts from different plants were coarsely powdered and macerated in methanol to obtain their crude extracts. The crude extracts were evaluated for their α-glucosidase inhibitory activity. On the basis of results obtained, the methanolic crude extract of Corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 31 publications
(39 reference statements)
4
48
0
1
Order By: Relevance
“…Kidane et al [37] reported that the extraction of Psiadia punctulata leaves in a methanolic solvent produced an extract with high AGI activity. A similar result was found by Bhatia et al [38] who reported the high AGI activity of a methanolic extract of Cornus capitata Wall leaves. Extraction with aqueous methanol was shown to be better for the recovery of the largest amount of phenolic compounds from Moringa oleifera and rice bran, which are related to antioxidant activity [39,40].…”
Section: Discussionsupporting
confidence: 88%
“…Kidane et al [37] reported that the extraction of Psiadia punctulata leaves in a methanolic solvent produced an extract with high AGI activity. A similar result was found by Bhatia et al [38] who reported the high AGI activity of a methanolic extract of Cornus capitata Wall leaves. Extraction with aqueous methanol was shown to be better for the recovery of the largest amount of phenolic compounds from Moringa oleifera and rice bran, which are related to antioxidant activity [39,40].…”
Section: Discussionsupporting
confidence: 88%
“…The inhibition of these enzymes is able to delay the absorption of monosaccharides from dietary complex carbohydrates, preventing any sudden rise in mealinduced blood glucose level, and therefore are involved in controlling the glucose level in the blood 7 . This is well correlated with the interesting finding that reveals that the a-glucosidase enzyme inhibitor is capable of slowing carbohydrate digestion, resulting in less efficient glucose absorption and thus decreasing postprandial hyperglycaemia 8 .…”
Section: Introductionsupporting
confidence: 67%
“…The IC 50 value of sub fraction of chloroform of G . sylvestre against α-glucosidase is 85.73 ± 0.001 µg/mL and it is better as compared to extract of leaves of Petalostigma pubescens (IC 50 value of 167.83 ± 23.82 μg/mL) 26 and ethyl acetate fraction of Cornus capitata (IC 50 value of 50 μg/mL) 29 . The bioactive sub fraction derivative of F .…”
Section: Discussionmentioning
confidence: 94%